Competing by design the power of organizational architecture - Nadler, David A.; Tushman, Michael L. 1943- (Oxford Univ. Press, 1997)
This book offers managers a systematic means of analyzing their organizations and, in turn, building integrated organizations to achieve sustainable competitive advantage. It leads managers through the process of designing new and more flexible organizations that will provide a firm's competitive edge into the next millennium